Zeólitas hzsm-5 sintetizadas a partir de fontes alternativas de sílica e alumínio para desoxigenação dos produtos da pirólise da fibra de coco - Costa, Juliana Elionara Bezerra (2017)
Some waste, from the most varied activities, can be reused, reducing the effect of these impacts, usually caused by poor disposal in the environment. The residues classified with lignocellulosic biomass can be converted into chemical products and fuels from the conventional fast pyrolysis, generating as main product the bio-oil. This generally presents some undesirable characteristics directly linked to the characteristics of the source biomass, which decrease its energy efficiency. The use of catalysts allows the reduction of these undesirable products and improves the final quality of the bio oil. As a result, ZSM-5 and HZSM-5 catalysts were synthesized using granite powder, glass powder, diatomite and rice husk ash as alternative sources of silica and aluminum; was also synthesized using a conventional silica and aluminum source, serving as a standard for the others. . The objective of the synthesis of these materials is to use them as a catalyst in the pyrolysis of coconut fiber in order to obtain products with higher added value, reducing the production of oxygenated compounds. The biomass used was characterized by immediate analysis, density, elemental analysis, cellulose content, hemicellulose and lignin, calorific power, TG / DTG, XRD, FT-IR and FRX in order to analyze the energy potential of the same. Silica and Aluminum precursors were subjected to FRX, XRD analyzes, and the catalysts were characterized by TG / DTG, DRX, FT-IR, MEV and BET. In the results of conventional pyrolysis of the coconut fiber, it was observed the great production of oxygenated products, most of them phenols and in the results of the catalytic pyrolysis it was possible to observe the decrease of these products, proving the efficiency of the catalysts used.